Demographic Aspects of Illiteracy in Italian Regions Through the Latest Census Data (Global Journal of Management and Business Research, 2025)
Abstract - The level of education is becoming more and more important in order to explain the variations in the demographic phenomena In fact many studies have shown that women with a high level of education have fewer children higher education is associated with lower mortality and better health These evidences are already consolidated in the recent international literature and according to many scholars the variable education wiIl be at the center of the social demography of the 21 st century In this context the analysis of illiteracy would allow to grasp some critical issues related to the transformations taking place in society We recall that in Italy the community of statisticians and demographers apart a brief interlude in the fifties and sixties of the last century gave little importance to the study of illiteracy considering it a residual element of the social development of the country Instead pedagogues and linguists because of their direct involvement have shown that in Italy illiteracy and functional illiteracy are in various ways widely spread and cause social marginalization
Keywords: demography; illiteracy; ltalian censuses